Eco-Efficiency of Pencil Preduction Using Life Cycle Assessment to Increase the Manufacture Sustainability - Purwaningsih, Ratna; Simanjuntak, Christoper Frans; Rosyada, Zainal Fanani (Jurnal Teknik Industri: Jurnal Keilmuan dan Aplikasi Teknik Industri, 2020)
This study aims to measure the environmental costs (eco-cost) and the eco-efficiency ratio rate (EER) of the production of pencils and formulate some recommendations to improve the manufacture sustainability. The measurement of Eco-efficiency was performed using life cycle assessment (LCA) with the eco-cost method. The pencil manufacturer produces a waste of 20 %, and the product rejects 37 %. The material used is wood, slat, and chemical material for painting. The result of the data processing shows that the eco-costs of IDR 50.593.583 for 4200 grosses production lot size. The eco-efficiency index or EEI for pencil product was 1,69, which means that the products are affordable and sustainable. The eco-efficiency ratio rate (EER) is 41% means that pencil production processes need improvement. The single score Impact Category Diagram shows that the most significant environment impact category is climate change. The recommendation to improve the EER of pencil production based on Impact Category Diagram is (1) to increase the utilizing of wood waste and (2) to increase the capability of technicians and operators to reduce the product rejection. These recommendations aim to reduce the wood consumed in production.